A lambda-graph system for the Dyck shift and its K-groups - Krieger, Wolfgang; Matsumoto, Kengo (Documenta mathematica, 2003)
A property of subshifts is described that allows to associate to the subshift a distinguishied presentation by a compact Shannon graph. For subshifts with this property and for the resulting invariantly associated compact Shannon graphs and their lambda-graph systems the term 'Cantor horizon' is proposed.